The effect of schooling and ability on achievement test scores - Karsten T Hansen; James J Heckman; Kathleen J Mullen (Institute for Labour Market Policy Evaluation (IFAU), 2003)
This paper develops two methods for estimating the effect of schooling on achievement test scores that control for endogeneity of schooling by postulating that both schooling and test scores are generated by a common unobserved latent ability. These methods are applied to data on schooling and test scores. Estimates from the two methods are in close agreement. We find that the effects of schooling on test scores are roughly linear across schooling levels. The effects of schooling on measured test scores are slightly larger for lower latent ability levels. We find that schooling increases the AFQT score on average between 2 and 4 percentage points, roughly twice as large as the effect claimed by Herrnstein and Murray (1994) but in agreement with estimates produced by Neal and Johnson (1996) and Winship and Korenman (1997). We extend the previous literature by estimating the impact of schooling on measured test scores at various quantiles of the latent ability distribution.
Keywords: C15; C35; I21; 330; Education; ability; latent variables; selection; MCMC